ABERRANT REWARD CENTER RESPONSE TO PARTNER REPUTATION DURING A SOCIAL EXCHANGE GAME IN GENERALIZED SOCIAL PHOBIA. Issue 4 (10th April 2013) - Sripada, Chandra; Angstadt, Michael; Liberzon, Israel; McCabe, Kevin; Phan, K. Luan
<x xml:space="preserve">Abstract</x> Objective Generalized social anxiety disorder (GSAD) is characterized by excessive fear of public scrutiny and reticence in social engagement. Previous studies have probed the neural basis of GSAD often using static, noninteractive stimuli (e.g., face photographs) and have identified dysfunction in fear circuitry. We sought to investigate brain‐based dysfunction in GSAD during more real‐world, dynamic social interactions, focusing on the role of reward‐related regions that are implicated in social decision‐making. Methods Thirty‐six healthy individuals (healthy control [HC]) and 36 individuals with GSAD underwent functional magnetic resonance imaging (fMRI) scanning while participating in a behavioral economic game ("Trust Game") involving iterative exchanges with fictive partners who acquire differential reputations for reciprocity. We investigated brain responses to reciprocation of trust in one's social partner, and how these brain responses are modulated by partner reputation for repayment. Results In both HC and GSAD, receipt of reciprocity robustly engaged ventral striatum, a region implicated in reward. In HC, striatal responses to reciprocity were specific to partners who have consistently returned the investment ("cooperative partners"), and were absent for partners who lack a cooperative reputation. In GSAD, modulation of striatal responses by partner reputation was absent. Social anxiety severity predicted diminished responses to cooperative partners. Conclusion These results suggest abnormalities in GSAD in reward‐related striatal mechanisms that may be important for the initiation, valuation, and maintenance of cooperative social relationships. Moreover, this study demonstrates that dynamic, interactive task paradigms derived from economics can help illuminate novel mechanisms of pathology in psychiatric illnesses in which social dysfunction is a cardinal feature.